2021
DOI: 10.3390/antiox10122029
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Biliverdin Reductase a Deficiency in Ugt1−/− Mice: Impact on Redox Status and Metabolism

Abstract: Accumulation of neurotoxic bilirubin due to a transient neonatal or persistent inherited deficiency of bilirubin glucuronidation activity can cause irreversible brain damage and death. Strategies to inhibit bilirubin production and prevent neurotoxicity in neonatal and adult settings seem promising. We evaluated the impact of Bvra deficiency in neonatal and aged mice, in a background of unconjugated hyperbilirubinemia, by abolishing bilirubin production. We also investigated the disposal of biliverdin during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Device and gate groups show no abnormal accumulation of dissolved Mg, Si, and Fe in organ tissues compared to control group ( SI Appendix , Tables S5 and S6 for analysis). SI Appendix , Supplementary Note 4 discussed the possible reasons ( 56 58 ) for elemental changes in spleen (for Si, Fe, SI Appendix , Fig. S20 ) and heart (for Si), from 1-wk to 4-wk endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Device and gate groups show no abnormal accumulation of dissolved Mg, Si, and Fe in organ tissues compared to control group ( SI Appendix , Tables S5 and S6 for analysis). SI Appendix , Supplementary Note 4 discussed the possible reasons ( 56 58 ) for elemental changes in spleen (for Si, Fe, SI Appendix , Fig. S20 ) and heart (for Si), from 1-wk to 4-wk endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies found a positive effect of the inactivation of Blvra to treat heme-metabolism-related human diseases, including neonatal jaundice and unconjugated hyperbilirubinemia in adults. Inhibition of Blvra is considered to be a novel promising and safe treatment for these pathologies (Bortolussi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a study reported that bilirubin had a strong antioxidant effect at a concentration below 100 nanomoles per liter (nM), which can protect nerve cells from oxidative stress damage [ 7 ]. On the other hand, high bilirubin levels can exhibit significant pro-oxidant and neurotoxic effects, ultimately leading to neuronal necrosis or apoptosis [ 8 , 9 ]. The dysfunction of the oxidative system may be involved in the pathogenesis of schizophrenia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%